Interest rates volatility impact on Malaysian Commercial Banks' deposit and lending rates / Illy Syazlina Musa (Faculty of Business and Management, 2008)
The volatility of interest rates can impact financial institutions in several different ways. It is called as the interest rate risk. Interest rate risk is defined as the adverse impact of interest rate movements on an institution's net interest income and market value. This paper examines the existence and the severity of interest rate risk on Malaysian Commercial Banks through the analysis of cycles in market rates and its impact on bank loans and deposit rates. The data that were used in this study is sourced from Bank Negara Malaysia's monthly bulletins. It covers the aggregate balance sheet of all commercial banks in Malaysia over a period of 20 years (1985-2004). Monthly observation of Kuala Lumpur Inter bank Offer rates (KLIBOR) and Malaysian Treasury Bills rates were used as proxies to the open market rates. The regression and correlation analysis was conducted in testing the impact of market rates movement on the asset and liability rates. Descriptive Statistic also was used to identify the severity of the interest rates. Market rates (T-Bills 3 month, T-Bills 12 month, Inter bank overnight and Inter bank 1 week) will be used as independent variable and Fixed Deposit rates and Average Lending rates will be used as dependent variable. The finding from this study shows that all dependent variable which are Fixed Deposit Rates and Average Lending Rates have a positive relationship and statistically significant effect with those four market rates which are T-Bills 3 month, T-Bills 12 month, Inter bank 1 week and Inter bank overnight. It shows that all null hypotheses in this study are rejected. We also can see that, lending rate which is Average Lending Rate is more influenced by the more volatile market rate which is Inter bank 1 week (67.9%). While deposit rate which is Fixed Deposit Rate is more influenced by the Inter bank overnight. This is among the more volatile market rate (78.4)